Predictive factors of response to liraglutide in patients with type 2 diabetes mellitus and metabolic syndrome - Song, Jinfang; Li, Na; Zhuang, Yongru; Chen, Ya; Zhang, Chu; Zhu, Jian (Frontiers in Endocrinology, 2024)
Background: Although liraglutide has established advantages in treating patients with type 2 diabetes mellitus (T2DM) and metabolic syndrome (MS), there are still some patients with lower responsiveness to liraglutide. The objective of the study was to identify the predictors of response to liraglutide in patients with T2DM and MS. Methods: This retrospective cohort study included patients diagnosed with T2DM and MS who received liraglutide treatment as a part of their diabetes management for a minimum of six months. The participants were stratified into two groups: responders (HbA1c reduction≥1.0% and weight loss≥3%) and non-responders. The discrepancies in baseline data between the two groups were analyzed, containing comedications, test parameters, and basic profiles. The affecting factors of response to liraglutide by Logistic regression analysis were performed, and the predictive ability of the identified factors was evaluated by plotting a receiver operating characteristic (ROC) curve. Results: A total of 417 patients with T2DM and MS were examined and followed up according to the inclusion criteria, and 206 patients completed the follow-up; 105 (50.97%) were responders and 101 (49.03%) were non-responders to liraglutide. The binary logistic regression analysis identified baseline HbA1c, baseline BMI, and the duration of T2DM as significant predictors of glycemic and weight responses to liraglutide (P <0.05). The area under the curve of the ROC for the three predictors of liraglutide response after 6 months of treatment was 0.851 (95% confidence interval: 0.793 - 0.910). Conclusion: The baseline HbA1c, baseline BMI, and duration of T2DM were shown to be predictive factors of glycemic and weight improvements in patients with T2DM and MS treated with liraglutide, and had good predictive power.